2009
DOI: 10.1007/s00063-009-1091-x
|View full text |Cite
|
Sign up to set email alerts
|

Twice Daily Fractionated Dose Administration of Prednisolone Compared to Standard Once Daily Administration to Patients with Glomerulonephritis or with Kidney Transplants*

Abstract: Twice daily fractionated administration of prednisolone allows a lower daily dose (total 2.5 mg/day), and appears to be as efficient but less diabetogenic compared to the standard once daily dosing (4.0 mg/day).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…There is currently no trial evidence to support the use of pharmacological therapy to delay or prevent the development of PTDM in kidney transplant recipients, although a small proofof-concept trial of 50 kidney transplant recipients without diabetes showed that the prescription of basal insulin in the immediate post-transplant period may reduce the incidence of PTDM, possibly by insulin-mediated protection of beta cells (127). Even though immunosuppressive agents have been shown to predispose to the development PTDM, it remains unclear whether the modification of immunosuppressive regimen (e.g., changing from tacrolimus to alternate agents; avoidance, minimization, or split dosing of corticosteroids) can reduce diabetogenic effect or consistently reverse the presence of established PTDM without resulting in a greater risk of other adverse allograft outcomes such as rejection and allograft loss (211)(212)(213)(214)(215)(216)(217). The benefit of lifestyle intervention (for weight reduction) or the use of "preventive" pharmacologic treatments including metformin, DPP4-inhibitor, and thiazolidinediones to reduce the risk of progression from a pre-diabetic state to type 2 diabetes in the general population has not been shown for kidney transplant recipients, but these approaches are currently being evaluated in this population group (218)(219)(220)(221)(222)(223).…”
Section: Management Of Kidney Transplant Recipients With Ptdmmentioning
confidence: 99%
“…There is currently no trial evidence to support the use of pharmacological therapy to delay or prevent the development of PTDM in kidney transplant recipients, although a small proofof-concept trial of 50 kidney transplant recipients without diabetes showed that the prescription of basal insulin in the immediate post-transplant period may reduce the incidence of PTDM, possibly by insulin-mediated protection of beta cells (127). Even though immunosuppressive agents have been shown to predispose to the development PTDM, it remains unclear whether the modification of immunosuppressive regimen (e.g., changing from tacrolimus to alternate agents; avoidance, minimization, or split dosing of corticosteroids) can reduce diabetogenic effect or consistently reverse the presence of established PTDM without resulting in a greater risk of other adverse allograft outcomes such as rejection and allograft loss (211)(212)(213)(214)(215)(216)(217). The benefit of lifestyle intervention (for weight reduction) or the use of "preventive" pharmacologic treatments including metformin, DPP4-inhibitor, and thiazolidinediones to reduce the risk of progression from a pre-diabetic state to type 2 diabetes in the general population has not been shown for kidney transplant recipients, but these approaches are currently being evaluated in this population group (218)(219)(220)(221)(222)(223).…”
Section: Management Of Kidney Transplant Recipients With Ptdmmentioning
confidence: 99%
“…An uncontrolled observational study of people with glomerulonephritis and ater kidney transplants appeared to support this notion because patients receiving twice daily fractionated doses of oral prednisolone had a decreased magnitude of proteinuria and a lesser requirement for additional immunosuppressive drugs compared with once daily dosing. 9 Conversely, more frequent administration of prednisolone results in greater adrenocortical suppression in dogs, 10 and may also increase the risk of typical adverse efects, including polyuria, polydipsia, polyphagia, excessive panting, muscle weakness and muscle wastage. 6 Previous studies have not focused on the impact these adverse efects could have on the quality of life (QoL) of the patient and their owner, even though these could have a substantial impact on the owner's decision to pursue treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship suggests that twice daily administration of prednisolone may increase its efficacy for management of autoimmune diseases by increasing its availability at the receptor site. An uncontrolled observational study of people with glomerulonephritis and after kidney transplants appeared to support this notion because patients receiving twice daily fractionated doses of oral prednisolone had a decreased magnitude of proteinuria and a lesser requirement for additional immunosuppressive drugs compared with once daily dosing 9 …”
Section: Introductionmentioning
confidence: 99%